Molecular Evidence Confirms the Taxonomic Separation of Lutzomyia tihuiliensis from Lutzomyia pia (Diptera: Psychodidae) and the Usefulness of Pleural Pigmentation Patterns in Species Identification. (2019)
Artículo digital.